598.191: Rapport van Hendrik de Man aan Henry J. Crowe over "Location of a Site for a Pulp and Paper Mill, Town and Harbour in Bay d’Espoir, Newfoundland/Canada" - Fonds Familie De Man
"Collection: Familie de Man; Series: 598.A.7.3: Expeditie New-Foundland (1919-1920); Level of description: File"